Knowledge and Attitude of Nurses on Kangaroo Mother Care in Selected Hospitals of Dhangadhi - Bhattarai, Sarada; Thapaliya, Rekha (NPRC Journal of Multidisciplinary Research, 2025)
Background: Kangaroo Mother Care (KMC) is essential for reducing neonatal morbidity and mortality in preterm and low-birth-weight infants. However, inadequate knowledge among nurses can hinder its effective implementation. This study aims to assess nurses' knowledge and attitudes toward KMC in selected hospitals in Dhangadhi. Methods: A descriptive cross-sectional study was conducted in selected hospitals in Dhangadhi, using a non-probability purposive sampling technique to select the hospitals and wards. The study included a complete enumeration of 115 nurses. A self-administered structured questionnaire was used to gather information on Kangaroo Mother Care. The data was coded, entered into SPSS version 16, and analyzed using both descriptive and inferential statistics (Chi-square test). Results: The study revealed that 45.2% of nurses were aged between 20 and 25 years, with a mean age of 27.43±5.90 years. More than half (56.5%) had completed PCL nursing. Regarding knowledge of Kangaroo Mother Care, 36.5% of respondents had good knowledge, 43.5% had average knowledge, and 20.0% had poor knowledge. Additionally, 51.3% of respondents exhibited a positive attitude toward KMC. A significant association was found between knowledge levels and both work experience and hospital type. Furthermore, a significant association was observed between attitudes toward KMC and hospital type. Conclusion: In conclusion, nearly half of the respondents had an average level of knowledge, while more than half demonstrated a positive attitude toward Kangaroo Mother Care. Hospitals should implement comprehensive KMC protocols and targeted training to improve nurses' knowledge and attitudes.